Ocorrências entre literatura e música na lenda Tristão e Isolda e na ópera homônima de Richard Wagner - Oliveira, Aline Carrijo de (2012)
This work aims to study, comparatively, the narrative Tristan and Isolde and homonymous Richard Wagner‟s opera. This study, of inter artistic transposition, analyses two versions, namely Tristão e Isolda, by Fernandel Abrantes and O Romance de Tristão e Isolda, by Joseph Bédier (translated by Luis Claudio de Castro e Costa), to build a relationship between both plots, setting, characters and time, to justify the choice of the versions, deriving from a series of recovered fragments as representative of the myth of Tristan. After the text of this research, we offer a literary analysis of Tristan and Isolde opera libretto as well as a brief explanation of the artist‟s composition procedures and a presentation of music critics who have studied Wagner‟s work. In an attempt to show the established proximities between the legend and the opera, we shall analyze comparatively the observations made about the narrative and the opera under the inter artistic transposition concepts.